Best Answer

x2 - 4x - 9 = 0

∴ x2 - 4x = 9

∴ x2 - 4x + 4 = 13

∴ (x - 2)2 = 13

∴ x - 2 = ±√13

∴ x = 2 ± √13

Q: Solve x2 - 4x - 9 equals 0 by completing the square?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-12 (?)

-3

-4x-4 equals -16. Add 4 to both sides; -4x equals -12. Divide both sides by -4; x equals 3.

y=4x-8y=2x+10Substitute (4x-8) for y in the second equation and solve for x:4x-8=2x+102x=18x=9Now solve for y:y=4(9)-8=28(9,28)

Yes and x = 2+square root of 6 or x = 2-square root of 6

Related questions

Divide all terms by 3 so:- x2-4x = 5 Completing the square:- (x-2)2 = 9 x-2 = -/+3 x = -1 or x = 5

4x = 72.divide both sides by 4x = 18

-12 (?)

-3

4x to the sixth can be expanded to (4x * 4x * 4x)(4x * 4x * 4x) or (4x to the third)(4x to the third) the square root of the above would be 4x to the third

2y = 4x + 4y = 2x + 2

X is 6

x = 5

-4x-4 equals -16. Add 4 to both sides; -4x equals -12. Divide both sides by -4; x equals 3.

4x = 16Divide each side of the equation by 4:x = 4

y=4x-8y=2x+10Substitute (4x-8) for y in the second equation and solve for x:4x-8=2x+102x=18x=9Now solve for y:y=4(9)-8=28(9,28)

Yes and x = 2+square root of 6 or x = 2-square root of 6